Strength-ideas evidenced in the organizational discourse on sustainability - Henriques, Márcio Simeone; Sant'Ana, Lidiane Ferreira (Organicom, 2013)
From the perspective of organizational communication, this article focuses on the discursive strategies that companies use to reconcile their business and economic interests with the legal and social pressures for environmental responsibility. To understand the place of speech that they assume, an empirical study is conducted in order to examine the organizational discourse on the sustainability of three large companies that operate in Brazil, by means of three strength-ideas: responsibility for environmental impact generated by the company, adoption of practices for mitigating environmental damage and the incentive for adopting sustainable attitudes by other social actors.